A potential of propolis on major virulence factors of Cryptococcus neoformans. (October 2018) - Thammasit, Patcharin; Iadnut, Anupon; Mamoon, Ketsaya; Khacha-ananda, Supakit; Chupradit, Koollawat; Tayapiwatana, Chatchai; Kasinrerk, Watchara; Tragoolpua, Yingmanee; Tragoolpua, Khajornsak
Abstract: The present study was conducted to investigate the effects of a natural product from honeybees, named propolis, against Cryptococcus neoformans and its effect in the expression of putative virulence factors, such as capsular polysaccharides, melanin production and urease enzyme. Ethanol extract propolis (EEP) was first tested for its anti-cryptococcal activity and explored its impact on virulence factors in both phenotypes and enzyme activities. Moreover, the cryptococcal virulence genes were investigated using real time RT-PCR. The MIC value of EEP, 1 mg ml −1, displayed potent inhibition of C. neoformans cell viability. Of note is the high efficacy of sub-MIC concentrations (ranging from 0.5 to 0.125 mg ml −1 ) in decreasing the production of capsule, melanin, as well as laccase and urease enzyme activities. Importantly, EEP exhibited statistically decrease in the expression of gene-encoded virulence factors. In conclusion, EEP mediates C. neoformans growth inhibition and virulence factors by reducing the gene-encoding virulence-associated proteins and, thereby, disrupting the morphologic presence and attenuating their virulence. This study introduced EEP as regards anti-cryptococcal virulence factors activities; therefore, EEP would provide alternative ways of controlling the pathogenicity. Graphical abstract: Highlights: Propolis represents a promising interfere molecule in the main virulence of C. neoformans. Suppression of phenotypes and genes associated with main virulence factors was noticed in propolis-treated C. neoformans. Anti-virulence approaches as an alternative way for cryptococcosis treatment.